2021
DOI: 10.1200/jco.2021.39.15_suppl.4112
|View full text |Cite
|
Sign up to set email alerts
|

Final overall survival in the phase 3 NETTER-1 study of lutetium-177-DOTATATE in patients with midgut neuroendocrine tumors.

Abstract: 4112 Background: As demonstrated in the primary analysis of the phase 3 NETTER-1 trial, 177Lu-DOTATATE significantly prolonged progression-free survival (PFS) versus high-dose long-acting octreotide, with a HR of 0.18 (95% CI: 0.11, 0.29; p < 0.0001), in patients with advanced, progressive, well-differentiated, somatostatin receptor-positive midgut neuroendocrine tumors (NETs). Here we report final overall survival (OS) for NETTER-1. Methods: In this international open-label trial, eligible patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 0 publications
1
48
1
2
Order By: Relevance
“…In addition, 200 patients entered long-term follow up and could receive further anti-cancer treatment as needed, which showed a clinically meaningful improvement in median overall survival in the 177 Lu-DOTATATE group of 48 months compared to 36.3 months in the octreotide LAR group. Whilst this was not a statistically significant result, this may have been influenced by a high rate (36%) of cross-over of patients from the octreotide LAR group to the PRRT group [76]. Reassuringly, no new safety concerns were revealed during this long-term follow-up period.…”
Section: Peptide Receptor Radiotherapy: From 111 In To 177 Lumentioning
confidence: 78%
“…In addition, 200 patients entered long-term follow up and could receive further anti-cancer treatment as needed, which showed a clinically meaningful improvement in median overall survival in the 177 Lu-DOTATATE group of 48 months compared to 36.3 months in the octreotide LAR group. Whilst this was not a statistically significant result, this may have been influenced by a high rate (36%) of cross-over of patients from the octreotide LAR group to the PRRT group [76]. Reassuringly, no new safety concerns were revealed during this long-term follow-up period.…”
Section: Peptide Receptor Radiotherapy: From 111 In To 177 Lumentioning
confidence: 78%
“…Recent analysis showed clinically improved median OS of 48 vs. 36 months compared to the control arm. However, the difference was not statistically significant between both groups, probably because of the high rate of cross-over-treatment in the study (36%) [73]. A debatable point of the NETTER-1 study is whether the effect of PRRT has been potentiated by SSA.…”
Section: Somatostatin Analoguesmentioning
confidence: 83%
“…Although the results of the final analysis of the NETTER-1 study indicate that PRRT is safe and effective, and rarely causes serious toxicity [ 155 ], there is evidence that dosimetric evaluation can play an important role—especially in patients with risk factors for renal or hematological toxicity, or those presenting with comorbidities [ 63 , 120 , 121 ]. Moreover, several studies have shown that additional PRRT cycles (salvage therapy setting) or re-treatments can be safely performed following dosimetric estimations [ 156 , 157 , 158 , 159 ].…”
Section: Somatostatin Analogues For Targeted Therapymentioning
confidence: 99%